Focus diagnostica. (Hasselt : Beta ventures)
Focus Diagnostica is the leading Belgian magazine on laboratory medicine.
Vanaf 2013 opgenomen in: Health Executive
Keywords: Laboratoriumtechnieken; Medische tijdschriften